2022
DOI: 10.3390/buildings12040397
|View full text |Cite
|
Sign up to set email alerts
|

Generating Inclusive Health Benefits from Urban Green Spaces: An Empirical Study of Beijing Olympic Forest Park

Abstract: Nature proximity contributes to improving many people’s health. In urban areas, how to increase the gaining of health benefits from urban green space (UGS) has gradually become a topic of concern for urban planners and public health practitioners. However, studies that can make causal inferences and evidence from developing countries and societies are still limited, and little has been done to address the issue of equity. Using data gathered in face-to-face surveys from 997 visitors to the Beijing Olympic Fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…[50] found that park use led to exercise and physical activity and to improvement in mood; ref. [147] found that green infrastructure fosters spirituality and wellbeing; and [148] presented findings which advocate that increased use of GSs promote our psychological health. Even though most of the aforementioned factors (proximity availability and exposure) were included in our hypothesis, we did not observe correlations with either mental health or restoration.…”
Section: Discussionmentioning
confidence: 99%
“…[50] found that park use led to exercise and physical activity and to improvement in mood; ref. [147] found that green infrastructure fosters spirituality and wellbeing; and [148] presented findings which advocate that increased use of GSs promote our psychological health. Even though most of the aforementioned factors (proximity availability and exposure) were included in our hypothesis, we did not observe correlations with either mental health or restoration.…”
Section: Discussionmentioning
confidence: 99%
“…To make the transition to satisfactory and sustainable mobility in cardependent cities, the reduction in car use should be accompanied by benefits for residents. These benefits include improved public transport, convenient walking and cycling, and an integrated system of public transport modes [11][12][13].…”
Section: The Growing Number Of Cars In European Citiesmentioning
confidence: 99%
“…Accessibility is also considered as a five-dimensional concept, encompassing approachability, acceptability, availability and accommodation, affordability, and appropriateness (Usher, 2015). Therefore, assessing park attractiveness should involve multiple factors beyond size and quality (He et al, 2022; Sundevall and Jansson, 2020), emphasizing on factors related to inclusiveness, particularly those relevant to the local context (Liang and Zhang, 2017). For instance, previous studies have shown that park entry fees in developing countries act as a barrier for low-income groups, significantly impacting their park visits (Lal et al, 2017; Pinelo Silva, 2021).…”
Section: Improving Gravity-based Accessibility Modelsmentioning
confidence: 99%